The problem of obesity and overweight among children and youth in the world - Chilimoniuk, Zuzanna; Borkowska, Aleksandra; Chałupnik, Aleksandra; Raksa, Karolina; Sobstyl, Anna; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Childhood obesity is one of the most difficult public health issues. According to "The Lancet" magazine, there are 124 million obese children in the world. The frequency of this disease in developed countries, including Poland, is constantly increasing. We can already talk about the obesity epidemic. Despite additional diseases, obesity has an economic impact in terms of combating its complications. Therefore, it is necessary to search for unknown risk factors as well as methods of their treatment. In order to obviate this disease, more and more preventive actions are being organised. However, education is not enough - joint actions undertaken by the authorities, society and representatives of the food industry are needed.